2016
DOI: 10.1016/j.jid.2016.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Independent Loss of Methylthioadenosine Phosphorylase (MTAP) in Primary Cutaneous T-Cell Lymphoma

Abstract: Methylthioadenosine phosphorylase (MTAP) and the tumor suppressor genes CDKN2A-CDKN2B are frequently deleted in malignancies. The specific role of MTAP in cutaneous T-cell lymphoma subgroups, mycosis fungoides (MF) and Sézary syndrome (SS), is unknown. In 213 skin samples from patients with MF/SS, MTAP copy number loss (34%) was more frequent than CDKN2A (12%) in all cutaneous T-cell lymphoma stages using quantitative reverse transcription PCR. Importantly, in early stage MF, MTAP loss occurred independently o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…A handful of clinical studies have found deletions of the MTAP gene without concordant loss of CDKN2A or CDKN2B , and its deletion rate is higher than that of CDKN2A in certain cancers. 18,23 In this study, we verified an indispensable role of MTAP loss in RCC progression. In our clinical observations, we show that a significant percentage of RCC tumors have low MTAP expression and that MTAP expression is inversely associated with tumor grade and shortens patient survival.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A handful of clinical studies have found deletions of the MTAP gene without concordant loss of CDKN2A or CDKN2B , and its deletion rate is higher than that of CDKN2A in certain cancers. 18,23 In this study, we verified an indispensable role of MTAP loss in RCC progression. In our clinical observations, we show that a significant percentage of RCC tumors have low MTAP expression and that MTAP expression is inversely associated with tumor grade and shortens patient survival.…”
Section: Discussionsupporting
confidence: 67%
“…Many studies have reported a lack of MTAP in numerous human tumors, including melanoma, gliomas, hepatocellular carcinoma, and pancreatic, lung, breast, and blood-related cancers. 18,20–27 However, the molecular mechanisms underlying MTAP-mediated tumor suppression have yet to be elucidated. Alarmingly, the function of MTAP in various cancers has been conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Several whole exome sequencing analysis reported a high rate of C>T transition in SS point mutations suggesting a causal role for UV exposure [ 25 , 37 ]. In our cohort, 6 out of 7 point mutations corresponded to a C>T transition.…”
Section: Resultsmentioning
confidence: 99%
“…Имеютсясведенияодисрегуляциинекоторыхгенов и их сигнальных путей при ТКЛК, но точно их роль впатогенезезаболеваниянеизвестна [4,5,17,23,[42][43][44][45][46][47][48][49][50][51][52][53][54][55].Нарушениеэкспрессииилифункциинегативных регуляторов,включаяSOCS3ипротеинтирозинфосфатазы,такиекакSHP1,вовлеченовдисрегуляциюпути Jak-3 / STATиинтерлейкиннезависимойпролиферации злокачественныхТ-клеток.АктивностьпутиJak-3 / STAT препятствуетразвитиюТКЛКчерезстимуляциюсинте-заIL-5,IL-10,IL-17AиIL-17F,регулированиефакторов ангиогенезаипрепятствуетрезистентностиктерапии ингибитором гистоновой дезацетилазы (histone deacetylaseinhibitor,HDACI) [48,51,56,57].Дополнительно сообщается о вовлечении в патогенез СС сиг-нальногопутиNOTCH1 [23,58].NOTCHвключаетсемейство трансмембранных рецепторов, которые регулируюттранскрипциюгенов,участвующихвэмбриональном развитии, гомеостазе тканей, дифференцировкеклетокиихвыживаемости [45].…”
Section: этиология и патогенезunclassified